Synthesis and Antioxidant Evaluation of Enantiomerically Pure Bis-(1,2,3-triazolylmethyl)amino Esters from Modified α-Amino Acids - Juan I. Sarmiento-Sánchez; Adrián Ochoa-Terán; Ignacio A. Rivero (The Scientific World Journal)
The efforts for synthesis of enantiomerically pure bis-(1,2,3-triazolylmethyl)amino esters 6 are reported in good yields from an in situ generated α-azidomethyl ketone. Optimum experimental conditions were established for preparation of α-halomethyl ketones 10 and α-N,N-dipropargylamino esters 11, all derived from α-amino acids. The starting materials reacted under conventional click chemistry conditions, revealing a specific reactivity of bromomethyl ketones over chloromethyl ketones. The antioxidant activity of compounds 6 was assayed by DPPH method. The compound 6c with an IC50 of 75.57 ± 1.74 μg mL−1 was the most active. Technically, this methodology allows the preparation of a combinatorial library of analogues with different structural characteristics depending on the nature of the modified α-amino acids employed in the synthesis.